The effect of zirconium doping of cerium dioxide nanoparticles on pulmonary and cardiovascular toxicity and biodistribution in mice after inhalation. Issue 6 (3rd July 2017) - Dekkers, Susan; Miller, Mark R.; Schins, Roel P. F.; Römer, Isabella; Russ, Mike; Vandebriel, Rob J.; Lynch, Iseult; Belinga-Desaunay, Marie-France; Valsami-Jones, Eugenia; Connell, Shea P.; Smith, Ian P.; Duffin, Rodger; et al.
Abstract: Development and manufacture of nanomaterials is growing at an exponential rate, despite an incomplete understanding of how their physicochemical characteristics affect their potential toxicity. Redox activity has been suggested to be an important physicochemical property of nanomaterials to predict their biological activity. This study assessed the influence of redox activity by modification of cerium dioxide nanoparticles (CeO2 NPs) via zirconium (Zr) doping on the biodistribution, pulmonary and cardiovascular effects in mice following inhalation. Healthy mice (C57BL/6 J), mice prone to cardiovascular disease (ApoE −/−, western-diet fed) and a mouse model of neurological disease (5 × FAD) were exposed via nose-only inhalation to CeO2 NPs with varying amounts of Zr-doping (0%, 27% or 78% Zr), or clean air, over a four-week period (4 mg/m 3 for 3 h/day, 5 days/week). Effects were assessed four weeks post-exposure. In all three mouse models CeO2 NP exposure had no major toxicological effects apart from some modest inflammatory histopathology in the lung, which was not related to the amount of Zr-doping. In ApoE −/− mice CeO2 did not change the size of atherosclerotic plaques, but there was a trend towards increased inflammatory cell content in relation to the Zr content of the CeO2 NPs. These findings show that subacute inhalation of CeO2 NPs causes minimal pulmonary and cardiovascular effect four weeks post-exposure and that Zr-doping of CeO2 NPs has limited effect on these responses. Further studies with nanomaterials with a higher inherent toxicity or a broader range of redox activities are needed to fully assess the influence of redox activity on the toxicity of nanomaterials.